Time to Talk? How the Structure of Dialog Processes Shapes Stakeholder Learning in Participatory Water Resources Management - Muro, Melanie; Jeffrey, Paul (The Resilience Alliance, 2012)
Public participation is increasingly viewed as a means to initiate social learning among stakeholders, resource managers, and policy makers rather than to ensure democratic representation. This growing understanding of participatory activities as learning platforms can be seen as a direct response to shifts in how natural resources management is framed, namely as uncertain, non-linear, and interlinked with the human dimensions. Social learning as it is discussed within the natural resources management (NRM) context features a process of collective and communicative learning that is thought to enable stakeholders to arrive at a shared understanding of a specific environmental situation and to develop new solutions as well as ways of acting together in pursuit of a shared ambition. Yet, although case-study research on social-learning processes provides multiple accounts of positive experiences, there are also reports of mistaken learning, the intensification of tensions or conflict, and failure to reach agreement or verifiable consensus. Based on results of a postal survey of stakeholder experiences in two involvement initiatives, we can draw two main conclusions: First, social learning is a multidimensional and dynamic process and, as such, evolves in stages and to various degrees. Second, stakeholder processes are shaped and affected by a multitude of factors that constrain the occurrence of learning processes and eventually limit the extent to which these can contribute to sustainable NRM. Foremost, the fact that the intensity of stakeholder learning differed in the two investigated initiatives reinforces the role organizational arrangements play in encouraging the type of communicative process necessary for stakeholder learning.
Keywords: participation; social learning; water framework directive